The Effect of Technical Efficiency on The Competitiveness of Cassava Indonesia - Yohana Julina Sinaga; Nunung Kusnadi; Dwi Rachmina (Jurnal Manajemen & Agribisnis, 2021)
Over the past 10 years, cassava imports in the form of semi-finished products have tended to increase. This study aims to analyze the comparative advantages and competitive advantages of fresh cassava at the farming and processed cassava level in the processing industry. The research used secondary data covering 2.595 cassava farmers in all provinces in Indonesia obtained from Agricultural Census 2013 - Central Bureau of Statistics (BPS), while data on the cassava processing industry was obtained from the publication of Bank Indonesia. The Policy Analysis Matrix (PAM) method was used to measure cassava's comparative and competitive advantages and further analyzed based on the technical efficiency score of the farm allegedly by the Data Envelopment Analysis (DEA) method. Results from PAM Analysis showed that Indonesian cassava products both in the farming and processing industry levels were not competitive. The technical efficiency of cassava production becomes the determinant of competitiveness the more efficient the production at the farm level, the competitiveness of cassava the higher. The competitiveness of the cassava processing industry is determined by the government's intervention in the price of cassava. The cassava processing industry pays for raw materials higher than it should. The implications of this study are to improve the competitiveness of Indonesian cassava products need to increase the efficiency of cassava farming production and government policies related to the selling price of fresh cassava to protect farmers and the cassava processing industry. Keywords: competitiveness, policy analysis matrix, technical efficiency, cassava